Severe Chronic Cough after Lap-Band Gastric Surgery - Jacqueline Nemni (Canadian Respiratory Journal)
Respirologists are often consulted in cases of chronic cough. Most patients have diagnoses of asthma, upper airway cough or gastroe-sophageal reflux disease. The present case describes a newly recognized cause of a cough in a patient who had undergone laparoscopic adjustable gastric banding for weight loss. The cough was persistent and severe for several months, and did not respond to any therapeutic interventions. Imaging studies were not helpful in making the diagnosis, which was confirmed by deflating the Lap-Band, thereby eliminating the cough.